Review of Waypoint Database Management in the Cartography Unit of the Aeronautical Information Services - Naufal Afiq Shoga Rashifaldo; Maruli Sinaga, Togi Adnan; Putra, Gilang Trio (Jurnal Teknologi Kedirgantaraan, 2025)
This study aims to review the management of the waypoint database in the Cartography Unit of the Aeronautical Information Center, with a focus on maintaining the integrity, consistency, and accuracy of waypoint data as a crucial component of flight safety. The impetus for this research is the identification of data inconsistencies, including differences in coordinates and waypoint naming on aeronautical charts, which may pose risks to air navigation. A descriptive qualitative approach was used, employing participatory observation, in-depth interviews, documentation review, and gap analysis comparing actual practice with existing regulations. The findings indicate that the current workflow for waypoint database management remains informal, lacking written Standard Operating Procedures (SOP), mandatory independent verification mechanisms, and formal appointment of responsible personnel. These shortcomings undermine data quality and increase the risk of inconsistencies in critical data. Accordingly, this study recommends the immediate development and implementation of formal SOPs, the official designation of a database manager, and the adoption of independent verification processes to ensure the integrity of waypoint data as critical data in aviation safety